Novel complementation biosensors to investigate G protein-coupled receptor kinetics and signalling bias - Dijon, Nicola C (2022)
G protein coupled receptors (GPCRs) signal through a complex cellular network, with a range of temporally variable signalling responses generated by GPCR activation. Characterisation of GPCR ligands is generally taken from the ligand “affinity”, the ability to bind the receptor, and the ligand “efficacy”, the ability to activate signalling from the receptor. Often single timepoints are used to quantify ligand affinity and efficacy by being applied to pharmacological models. Biased ligands, which have been suggested to preferentially activate one signalling pathway over another, are often identified from comparisons of concentration response data of an agonist between single timepoints of assays measuring the activation of different signalling proteins. Existing pharmacological models, which estimate ligand potencies, efficacies and ligand bias, such as the Black and Leff operational model, from functional data assume system equilibrium, yet often concentration response data at early timepoints are taken from hemi-equilibrium conditions. More recently, appreciation of agonist binding kinetics and signalling kinetics at GPCRs has increased, enhancing the extent of ligand characterisation and used to investigate discrepancies in ligand bias between different experimental systems. The origin of ligand bias has been suggested to be conformational, where the agonist binds the receptor to allosterically promote the formation of a conformation which preferentially activates one signalling pathway over another. It has also been suggested that bias originates from different receptor binding kinetics, which produce different profiles of signalling and can confound comparisons of bias – especially when bias is compared from a single timepoint. In this thesis we investigate how signalling kinetics and binding kinetics can influence measures of ligand affinities, efficacy and bias using experimental system monitoring dynamic protein:protein and ligand-receptor interactions.